Respuesta :

Answer:

B. 7y - 15

Step-by-step explanation:

Simplifying

10y + -3(y + 5) = 0

Reorder the terms:

10y + -3(5 + y) = 0

10y + (5 * -3 + y * -3) = 0

10y + (-15 + -3y) = 0

Reorder the terms:

-15 + 10y + -3y = 0

Combine like terms: 10y + -3y = 7y

-15 + 7y = 0

Solving

-15 + 7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '15' to each side of the equation.

-15 + 15 + 7y = 0 + 15

Combine like terms: -15 + 15 = 0

0 + 7y = 0 + 15

7y = 0 + 15

Combine like terms: 0 + 15 = 15

7y = 15

Divide each side by '7'.

y = 2.142857143

Simplifying

y = 2.142857143

Answer:

b. 7y-15

Step-by-step explanation:

First, write out the expression

1. [tex]10y-3(y+5)[/tex]

To simplify the expression distribute the -3 to the terms within the paratheses.

2. [tex]10y-3y-15[/tex]

Then, combine like terms to simplify further. Since 10y and -3y are like terms they can be subtracted

3. [tex]7y-15[/tex]

This means that B is the correct answer.

ACCESS MORE